Iatrogenic Subclinical Hyperthyroidism Does Not Promote Weight Loss. Issue 2 (February 2016) - Kedia, Rohit; Lowes, Alicia; Gillis, Sarah; Markert, Ronald; Koroscil, Thomas
Abstract : Objectives: Among patients who have undergone total thyroidectomy, do those with thyroid cancer being kept iatrogenically subclinical hyperthyroid (SCH) differ from euthyroid patients in long-term weight change? Methods: In a retrospective study, medical records identified 291 patients who had undergone a thyroidectomy for differentiated thyroid cancer or benign thyroid disease. Weight, thyroid-stimulating hormone, and levothyroxine dose were measured presurgery and 1, 2, and 3 years postsurgery. Results: Of 291 patients, 147 were in the SCH group and 144 were in the euthyroid group. At all 3 years both groups gained weight from baseline, but the two groups did not differ in weight change from baseline at any time period: year 1 (SCH mean 0.4% ± 6.2% weight gain vs euthyroid group mean 2.2% ± 6.6% weight gain; P = 0.12), year 2 (SCH mean 1.1% ± 9.1% weight gain vs euthyroid mean 2.9% ± 7.8% weight gain; P = 0.22), and year 3 (SCH mean 2.6% ± 9.2% weight gain vs euthyroid mean 3.1% ± 11.1% weight gain; P = 0.49). Conclusions: Among total thyroidectomy patients, weight change did not differ between SCH patients and euthyroid patients at years 1 through 3. As such, the use of levothyroxine to induce SCH did not lead to long-term weight change when compared with euthyroid patients. Abstract : The changes in weight associated with thyroid hormone function have been postulated and debated; however, the mechanism remains unclear. This study is a retrospective review of the effect of iatrogenic subclinical hyperthyroidism or euthyroid thyroid hormone replacement in patients who have undergone total thyroidectomy. The data failed to demonstrate a weight loss effect in patients maintained on suppressive doses of levothyroxine.